Exploratory Study On Perceived Value Among Ott Viewers Of Mayiladuthurai District - P. Nisha; Dr. A. Karthikeyan (Revista Electronica de Veterinaria, 2024)
The rapid transformation of the media landscape from traditional broadcasting to Over-The-Top (OTT) streaming has necessitated a deeper understanding of consumer behaviour in digital environments. This exploratory study investigates the dimensions of Perceived Value—including entertainment quality, value for money, value for time, and user-friendliness—and their subsequent impact on Brand Loyalty among OTT viewers. Utilizing a quantitative research design, primary data was collected from a sample of 60 respondents via a structured questionnaire. While the Independent T-Test showed no significant difference in perceived value based on gender, the ANOVA results indicated that "Value for Money" and "Pricing" are critical factors that vary across income groups. Specifically, content variability and pricing were found to be the most influential drivers of shifting consumer perceptions. The study concludes that while content quality remains the primary driver of engagement, platforms must balance competitive pricing with user-centric interfaces to maintain long-term loyalty. The research suggests that OTT providers should adopt tiered pricing models and enhance content personalization to mitigate subscription fatigue and reduce churn rates in an increasingly saturated market.